Population Aging as the Social Body in Representation and Real Life - Alexandra Crampton (Anthropology & Aging, 2013)
This article uses three levels of body analysis as presented by Nancy Scheper-Hughes and Margaret Lock to compare old age as a construct in population aging discourse with research on lived experience of people aging in the United States and Ghana. I first describe how demographers construct social bodies as becoming “gray” through population statistics and how policy makers then use dependency ratios to rationalize intervention on behalf of older adults in the body-politic.  The construction of old age within this discourse is then compared with ethnographic research that suggests this construct leaves out much of the lived experience familiar to anthropologists of aging.  Rather than debunk the old age construct, however, the purpose of this article is to argue for study of population aging discourse as constituting a social body reflecting cultural constructions of nature and society.  Moreover, this representation is made real through policy and social intervention work, and with very real effect on people’s lives. As such, an anthropology of aging bodies can include the social life of old age as a social construct.